Investigating the genetic basis of autoimmune disease - Hodgson, R (2021)
The maintenance of immune tolerance is essential to prevent the initiation of inappropriate and potentially harmful responses by autoreactive lymphocytes. Autoimmune diseases are ultimately caused by a loss of tolerance to self; this can be driven by rare genetic variants; however, the aetiologies are more often complex, covering an incompletely understood combination of environmental, immunological and common genetic risk factors. Since rare monogenic disorders can illuminate mechanisms relevant to common disease, furthering our knowledge of the inherited mechanisms that affect tolerance loss may help to advance treatment options across many immune disorders, beyond current strategies of broad immunosuppression with limited efficacy and significant side effects. Using forward and reverse genetics approaches and engineered in vivo models, this thesis aims to establish whether two genes, N-myc Downstream-Regulated Gene 1 (Ndrg1) and Pepd, with apparent roles in the maintenance of immune tolerance, do alter the threshold for autoimmunity and begin to explore how this is mediated.